2001
DOI: 10.4049/jimmunol.167.5.2921
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Binds CpG-Containing Oligonucleotides and Inhibits Their Immunostimulatory Effects on Human B Cells

Abstract: Unmethylated CpG dinucleotide motifs in bacterial DNA, as well as oligodeoxynucleotides (ODN) containing these motifs, are potent stimuli for many host immunological responses. These CpG motifs may enhance host responses to bacterial infection and are being examined as immune activators for therapeutic applications in cancer, allergy/asthma, and infectious diseases. However, little attention has been given to processes that down-modulate this response. The iron-binding protein lactoferrin is present at mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 88 publications
0
57
0
2
Order By: Relevance
“…The mechanism by which a methylated plasmid is detected by immune cells still remains unknown. Recent studies have described that HSP90 and lactoferrin interact as well as with unmethylated and methylated DNA [46,47]. In addition, type A Scavenger receptor binds polyanionic compounds such DNA [48].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which a methylated plasmid is detected by immune cells still remains unknown. Recent studies have described that HSP90 and lactoferrin interact as well as with unmethylated and methylated DNA [46,47]. In addition, type A Scavenger receptor binds polyanionic compounds such DNA [48].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that LF has inhibitory effects on inflammatory responses. 16,18 In the present study, we first found that LF can inhibit EBV-induced IL-8 and MCP-1 expression in macrophages. Further, by means of qRT-PCR, we found that LF mRNA is absent or downregulated in most NPC tissues and its expression levels are negatively correlated with IL-8 or MCP-1 levels.…”
Section: Lf Expression Levels Correlated Inversely With Mcp-1 and Il-mentioning
confidence: 99%
“…[13][14][15] Although the cellular and molecular mechanisms accounting for the immunemodulatory effects of LF are far from being fully elucidated, it is now clear that the capacity of LF to influence cytokine production, either negatively or positively, relies, at least in part, on its ability to bind and sequester both lipopolysaccharide and its receptor CD14, as well as CpG DNA, thus preventing the downstream activation of pro-inflammatory pathways. [16][17][18] Through the linkage analysis of 18 pedigrees from the Hunan province of South China, we previously revealed that potential susceptibility loci related to NPC are located on chromosome 3p21. 19 Further isolation and identification of a list of new tumor-suppressor genes for NPC from this region were pursued and LF gene is one of the candidates.…”
mentioning
confidence: 99%
“…With acute mastitis, Lf is likely to participate in the bacteriostatic activity of cell-free milk, but only when milk composition has grossly changed, milk yield dramatically decreased, and Lf concentrations have considerably augmented [137]. The binding of Lf and its proteolysis fragments to LPS, LTA and CpG may dampen the inflammatory response during acute mastitis, to the host's benefit [20,200]. Lf inhibition of pro-inflammatory cytokines by monocytes stimulated by LPS may reduce the systemic inflammatory response and down regulate the activation of neutrophils in milk and mammary tissue, contributing to the protection of the MG from neutrophil-induced damages.…”
Section: Inducible Defensesmentioning
confidence: 99%
“…During acute mastitis, Lf is likely to participate in the bactericidal activity of cell-free milk, but only when milk composition has grossly changed, milk yield dramatically decreased, and Lf concentrations have considerably augmented. The binding of Lf and its proteolysis fragments to LPS, LTA and CpG may dampen the inflammatory response during acute mastitis, to the host's benefit [20,200].…”
Section: Humoral Defensesmentioning
confidence: 99%